Wendigos, Eye Killers, Skinwalkers: The Myth of the American Indian Vampire and American Indian “Vampire” Myths - Lenhardt, Corinna (Text Matters: A Journal of Literature, Theory and Culture, 2016)
We all know vampires. Count Dracula and Nosferatu, maybe Blade and Angel, or Stephenie Meyer’s sparkling beau, Edward Cullen. In fact, the Euro-American vampire myth has long become one of the most reliable and bestselling fun-rides the entertainment industries around the world have to offer. Quite recently, however, a new type of fanged villain has entered the mainstream stage: the American Indian vampire. Fully equipped with war bonnets, buckskin clothes, and sharp teeth, the vampires of recent U.S. film productions, such as Blade, the Series or the Twilight Saga, employ both the Euro-American vampire trope and denigrating discourses of race and savagery. It is also against this backdrop that American Indian authors and filmmakers have set out to renegotiate not only U.S. America’s myth of the racially overdrawn “savage Indian,” but also the vampire trope per se. Drawing on American Indian myths and folklore that previous scholarship has placed into direct relationship to the Anglo-European vampire narrative, and on recent U.S. mainstream commodifications of these myths, my paper traces and contextualizes the two oppositional yet intimately linked narratives of American Indian vampirism ensuing today: the commodified image of the “Indian” vampire and the renegotiated vampire tropes created by American Indian authors and filmmakers.